State of anticoagulant and fibrinolytic systems of blood in patients with hypertension in combination with non-alcoholic fatty liver disease - Bazhenova, Nataliia (ScienceRise: Medical Science, 2018)
Aim of the research. To determine the state of the anticoagulant and fibrinolytic activity of blood in patients with hypertension and concomitant non-alcoholic fatty liver disease. Methods. 132 patients were examined. 45 patients with hypertension stage II (HT) with concomitant non-alcoholic fatty liver disease (NAFLD), 31 patients with NAFLD without HT, 41 patients with HT without concomitant NAFLD. The control group - 15 healthy individuals of comparable age and sex. To achieve the aim the study of the anticoagulant and fibrinolytic link was carried out by special laboratory studies. Results. When compared with the control group, the level of Antithrombin III decreased by 16.4 % in the HT group (p<0.01) and in the NAFLD group (p<0.01), HT+NAFLD – by 20.3 % (p<0.001). The level of Protein C in patients with hypertension decreased by 26 % (p<0.001), with NAFLD – by 9.5 % (p<0.05), with NAFLD+HT – by 14.1 % (p<0.01). Plasminogen decreased in HT – by 15 % (p<0.001), NAFLD – by 20.9 % (p<0.001), NAFLD+HT – by 16.5 % (p<0.001). The duration of Hageman-dependent fibrinolysis is increased in all groups compared to control: in the HT group – by 47 % (p<0.001), in the NAFLD group – by 78 % (p<0.001), in the NAFLD+HT group – 2.4 times (p<0.001). Conclusions. Suppression of anticoagulant hemostasis is observed in patients with hypertension and with NAFLD. The decrease in the fibrinolytic activity of the blood system is reflected in the extension of the dissolution time of the fibrin clot in the group of patients with hypertension, NAFLD, NAFLD combined with HT. The level of plasminogen decreased to the same extent in patients with hypertension and with the combination of hypertension and NAFLD but isolated NAFLD had a stronger effect on this indicator. NAFLD is a risk factor for thrombophilic changes in the blood